ISLAMIC EDUCATION POLICY IN ISLAMIC BOARDING SCHOOLS TO ENCOUNTER THE FLOW OF GLOBALIZATION - Rozza, Dian Silvia; Arifin, Syamsul; Humaidi, M. Nurul; Danis, Ahmad (Universitas Indraprasta PGRI, 2024)
This research aims to describe and analyze public policies and Islamic boarding school education policies, especially Law No. 18 of 2019. Apart from that, it also discusses the challenges of Islamic boarding schools in the era of globalization which is the basis for the proposed Islamic boarding school policy formula. This research uses a qualitative approach with types of literature. The literature study was carried out by collecting and analyzing literature related to Islamic boarding school education policies. The research results explain that: (1) public policies related to Islamic boarding school education are contained in Law No. 18 of 2019. This Islamic boarding school law contains Islamic boarding school policy regulations which consist of nine chapters and 55 articles. If concluded, then this law can be categorized into five categories, namely: form of institution, objectives of Islamic boarding schools, funding sources, quality assurance, and level of education; (2) the influence of globalization can have an impact on an apathetic attitude and a culture of laziness for Islamic boarding school cadres in developing their potential. So Islamic boarding school cadres are needed who can develop their potential using science and technology, and (3) the preparation of policy formulas can be carried out using five procedures, namely: agenda setting, policy formulation, policy implementation, policy evaluation, and policy improvement. Thus, it is hoped that this research can become a reference for understanding in-depth educational policies and efforts to formulate Islamic boarding school education policy formula.